Epidemiological review of mental disorders in Perú - Torres Rodas, Senaida (2021)
This article was of great importance, because it makes known the reality of mental health that the citizens of our country go through. According to Epidemiological Studies of Mental Health (ESM) and the sectoral policy guidelines for mental health in Peru, it indicates that the highest annual prevalence of mental disorders is found and it has an incidence in urban areas of cities, especially in Ayacucho, Puerto Maldonado, Iquitos, Tumbes being there 20.7%; while in rural areas they are 10.4% in the rural region of Lima, according to the Ministry of Health (MINSA, 2018). With this information, we perceive that the incidence of mental problems is centered in cities, with rural areas being the ones with the lowest percentage with metal health problems. With regard to gender, women are more affected than men. Regarding the stages of human development, the elderly have the highest incidence with respect to the other age groups; followed by teenage infants. This study aimed to carry out the epidemiological analysis of mental disorders in Peru, through a systematic review of research conducted by MINSA, the National Institute of Mental Health "Honorio Delgado Noguchi" (INSM "HD-HN") and authors of various universities, which we are mentioning in this article.